Clinical observations and safety profile of oral herbal products, souroubea and platanus spp: a pilot-toxicology study in dogs - Villalobos, Pedro (2014)
This pilot-study evaluated the toxicity and safety profi le of two herbal products Souroubea spp Botanical Blend (SSBB) and Platanus Tree Bark (PTB) after oral administration to dogs at elevated doses for 28 days. SSBB and PTB botanicals are the major active ingredients of Sin Susto, a novel natural product for the treatment of anxiety in dogs. Three healthy female dogs were administered elevated doses of either SSBB, PTB or a placebo and then monitored for the occurrence of any systemic and local adverse events. Data from this pilot-study revealed that SSBB and PTB had no untoward effects on the health of dogs and were deemed safe which enabled the design and execution of a larger controlled target safety and toxicology study for Sin Susto.